Ghosts of the black decade: How legacies of violence shaped Algeria’s Hirak protests - KILAVUZ, MUHAMMET TAHİR (My University, 2023)
© The Author(s) 2023.Episodes of mass political violence, such as genocide and civil war, have been thought to both encourage and discourage future political mobilization. We square these competing hypotheses by disaggregating between protest onset and resilience. We argue that exposure to mass violence decades ago should on average decrease protest onset, by heightening fears of repression and retribution. However, conditional on protesting, prior exposure to violence should increase protest longevity, by generating greater political grievances that fuel commitment to the cause. We find evidence of both effects in Algeria during the 2019–20 Hirak protests that toppled President Abdelaziz Bouteflika. Pairing an original dataset on massacres during the 1990s civil war with a rolling online survey of 18,000 Algerians in 2019–20, we find that areas exposed to greater violence in the 1990s had on average fewer, but more committed, protesters in 2019–20.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Science, Technology and Society; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SOSYOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; SOCIOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; POLITICAL SCIENCE; Sosyoloji ve Siyaset Bilimi; Sosyal Bilimler ve Beşeri Bilimler; Güvenlik Araştırması; Siyasi bilimler ve Uluslararası İlişkiler; Sociology and Political Science; Social Sciences & Humanities; Safety Research; Political Science and International Relations; Algeria; legacies of violence; protest; revolution; survey